Occupation of a thermoresistant-scaffold (αRep) at SP1-NC cleavage site disturbs the function of HIV-1 protease. Issue 6 (23rd June 2020) - Hadpech, Sudarat; Peerakam, Nichakan; Chupradit, Koollawat; Tayapiwatana, Chatchai
Abstract: HIV-1 nucleocapsid (NC) becomes an attractive target for the development of novel anti-HIV-1 agents. Discovering of non-antibody scaffolds that disrupt the function of NC will be a potential aspect for disturbing viral maturation process. Correspondingly, we explored the specific binding site of the thermoresistant-scaffold protein, αRep9A8 which formerly demonstrated the inhibitory effect on HIV-1 replication. The portion of Gag, CA21 -SP1-NC has been used as a template for designing nine overlapping peptides (P4–P12). The P9 peptide showed the strongest binding activity followed by P8 and P12 respectively. The amino acid sequences on those peptides resemble the N-terminal domain of the NC proximity to the SP1-NC initial cleavage site and across the conserved CCHC zinc finger 1 (ZF1) of NC. The interaction K D between αRep9A8 with its target was 224.9 ± 57.4 nM. Consequently, αRep9A8 demonstrated the interference of the HIV-1 protease function by hindering a protease cleavage site. The released NC product from CA21 -SP1-NC was diminished. The present study provided an additional information of αRep9A8 function in interfering of viral maturation processes resulting in the decremental efficiency of viral infectivity.